PENGUATAN PROTOKOL KESEHATAN PENCEGAHAN COVID 19 DENGAN MENCUCI TANGAN DENGAN SABUN DAN MEMAKAI MASKER DI DESA KLAMPISAN, KECAMATAN GENENG, KABUPATEN NGAWI - Yudisa Diaz Lutfi Sandi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Background: Covid-19 pandemic has become a growing issue in Indonesia with erious attention from the government by providing a policy of implementing strict health protocols. There is a problem of high transmission which is causally due to the application of wearing masks and how to wash hands with soap that is not appropriate and facilities that are not balanced. Aims: The social service prevents the spread of Covid-19 through socializing and facilitating the community in carrying out health protocols by use mask and hand washing appropiately. Methods: Participants in community service selected by random sampling. selection of participants according to the advice of community leaders. Results: obtained as many as 70 people in Klampisan Village, Geneng District, Ngawi Regency by going from house to house by several implementing teams. the community received socialization and a package of health protocols in the form of masks and hand washing soap. The socialization was given through appeals and leaflets about preventing Covid-19 in the surrounding environment. Conclusion: health education,s appeal to prevent Covid-19 transmission and facilitate the use of masks and soap for washing hands as prevent Covid-19 in the future to leads awareness of implementing health protocols helps prevent Covid-19 in Kalmpisan Village, Geneng, Ngawi District.